Caregivers’ Perspectives on Human–Robot Collaboration in Inpatient Elderly Care Settings - Robert Klebbe; Kim Klüber; Rebecca Dahms; Linda Onnasch (Machines, 2022)
Due to serious challenges in the healthcare sector, high expectations are placed on the use of assistive robotics. However, only a few systems are currently commercially available. Key challenges in the automation of care activities concern the identification and robust mediation of medical and nursing standards as well as the distribution of agency between caregivers, robots, and patients. With regard to successful mediation of this relational framework, this research aims to identify (1) prerequisites for the implementation and use of robots, (2) potential areas of application as well as ethical considerations, and, finally, (3) requirements for the design of human–robot interactions (HRI) within inpatient elderly care settings. Using a qualitative research approach with semi-structured interviews, a total of 19 health professionals were interviewed in two constitutive studies. The results illustrate that robotic assistance is expected to provide potential relief in various application areas. At the same time, there was a great need for measures that support professionals in their responsibility for the care process and consider the professional values of care in the interpersonal relationship. To ensure high acceptance and use of robotics in care, its capabilities, role models, and agency must be increasingly aligned to professional standards and values.